ANALYSIS OF THE RECIPROCAL RELATIONSHIP OF LOCAL GOVERNMENT EXPENDITURE TOWARDS HUMAN DEVELOPMENT INDEX (HDI) AND ITS INFLUENCE ON ECONOMIC PERFORMANCE IN SOUTH SULAWESI - Nujum, Syamsu; Pyriadi, Annas; Nur, Muhammad (Journal of Humanity, 2016)
Analysis of the reciprocal Relationship of local GovernmentExpenditure towards human development index and its influence on economicperformance in South Sulawesi. The purpose of the research is to 1. Analyse theinfluence of the development expenditure against the human development index(HDI) 2. analyse the influence of the human development index against theperformance of construction economics, 3. The relationship of developmentspending on performance economic development. 4. The extent of theGovernments efforts in the construction of human resources in South Sulawesi.The data used are the primary data and secondary data, the method of analysisused was multiple Linear regression, this research was carried out on 4 CityDistricts in South Sulawesi. The results of the Penelitian human developmentindex in the city of Makassar 78.11 percent average during the period 2008-2013,higher than Regency Takalar and Gowa, Maros. The human development indexMakassar city showed no significant influence on performance development,currently, Takalar and Gowa Regency Maros simultaneously GRANT and HDImember influence significant, but does show the influence of partiallyproportionally in support of improved performance of economic development.Economic growth in the city of Makassar during 2008-2013 is experiencing apositive trend with the average the growth of the 9.66 percent and is the highestgrowth rate of Regency Takalar and Gowa, Maros